Abnormal frontal generator during auditory sensory gating in panic disorder: An MEG study. (30th June 2019) - Cheng, Chia-Hsiung; Chan, Pei-Ying S.; Hsu, Shih-Chieh; Liu, Chia-Yih
Highlights: Neural correlates of sensory gating (SG) deficits in PD are poorly understood. We used paired-click paradigm and MEG imaging to study SG function in STG and IFG. PD patients showed declined SG function in right STG and right IFG. SG of the right IFG was correlated with somatic symptoms and distractibility. We suggest PD patients showed reduced ability to filter out irrelevant information. Abstract: Patients with panic disorder (PD) exhibit abnormalities in early-stage information processing, even for the nonthreatening stimuli. A previous event-related potential study reported that PD patients show a deficit in sensory gating (SG), a protective mechanism of the brain to filter out irrelevant sensory inputs. However, there is no clear understanding about the neural correlates of SG deficits in PD. Moreover, whether SG deficits, if any, are associated with clinical manifestations remain unknown. In this study, 18 patients with PD and 20 age- and gender-matched healthy controls were recruited to perform auditory paired-stimulus paradigm using magnetoencephalographic (MEG) recordings. Results showed that PD patients demonstrated significantly higher M50 SG ratios in the right inferior frontal gyrus (RIFG) and higher M100 SG ratios in both RIFG and right superior temporal gyrus (RSTG) than those of the control group. It was important to note that in the RIFG, the M50 SG ratios correlated significantly with the scores of Body Sensation Questionnaire (BSQ) and Distractibility scale of Sensory Gating Inventory among patients with PD. In conclusion, this study suggests that PD patients exhibited a deficient ability to filter out irrelevant information, and such a defect might lead to cognitive misinterpretation of somatic sensations and distractibility.